Relationship of ventricular and atrial dilatation to valvular function in endurance athletes. Issue 3 (17th August 2009) - Prakken, N H; Velthuis, B K; Bosker, A C; Mosterd, A; Teske, A J; Mali, W P; Cramer, M J
Abstract : Objective: To establish cardiac magnetic resonance imaging (MRI) reference values for atrial adaptation to training in endurance athletes in comparison with matched non-athletes. In addition, to study the relationship of atrial size to ventricular and annular size and valvular function. Design: Cross-sectional study. Participants: 180 healthy individuals aged 18–39 years (41% women): 60 elite endurance athletes (exercising > 18 h/week), 60 regular endurance athletes (9–18 h/ week), and 60 age and gender matched non-athletes (exercising ≤3 h/week) underwent cardiac MRI. Quantitative atrial dimensions and volumes, indexed for body surface area (BSA), were compared with ventricular and annular dimensions. Regurgitant fractions of all four valves and peak velocities of mitral and tricuspid valves were also assessed. Results: BSA-corrected right and left atrial volumes and diameters were significantly larger for athletes compared with non-athletes (p<0.05–p<0.0005). Ventricular, annular and atrial ratios remained constant for all groups, suggesting balanced adaptation to exercise training. E/A ratios remained statistically unchanged in all groups. Regurgitant fractions of the four cardiac valves were all mild (≤15%) and not significantly different in athletes compared with non-athletes. Conclusions: Atrial remodelling in endurance athletes may be regarded as a balanced physiological adaptation to exercise training with preservation of valvular function.